Karel Schoeman, The Early Mission in South Africa: Die Vroeë Sending in Suid-Afrika, 1799-1819: The Early History of Missionary Activity in South Africa (Historia, 2021)
This work attempts to fill an important gap in the early history of missionary activity in South Africa. Unfortunately, it is only partly successful in doing so. I frequently found myself wishing that Schoeman had gone deeper and engaged many of the fascinating underlying issues which he skims over in attempting ..